2017
DOI: 10.1371/journal.pone.0176024
|View full text |Cite
|
Sign up to set email alerts
|

Cloning retinoid and peroxisome proliferator-activated nuclear receptors of the Pacific oyster and in silico binding to environmental chemicals

Abstract: Disruption of nuclear receptors, a transcription factor superfamily regulating gene expression in animals, is one proposed mechanism through which pollution causes effects in aquatic invertebrates. Environmental pollutants have the ability to interfere with the receptor’s functions through direct binding and inducing incorrect signals. Limited knowledge of invertebrate endocrinology and molecular regulatory mechanisms, however, impede the understanding of endocrine disruptive effects in many aquatic invertebra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 85 publications
3
25
0
Order By: Relevance
“…Contrasting the situation in annelids, mollusk RARs have lost the ability to bind RA. It has been suggested that mollusk RARs secondarily lost the capacity to bind RA by accumulating independent single mutations in different mollusk lineages [ 51 , 56 ]. Accordingly, mollusk RARs likely function as constitutive transcriptional repressors [ 50 , 51 , 102 ].…”
Section: Retinoic Acid Receptor (Rar)-dependent Signaling Is Requimentioning
confidence: 99%
See 1 more Smart Citation
“…Contrasting the situation in annelids, mollusk RARs have lost the ability to bind RA. It has been suggested that mollusk RARs secondarily lost the capacity to bind RA by accumulating independent single mutations in different mollusk lineages [ 51 , 56 ]. Accordingly, mollusk RARs likely function as constitutive transcriptional repressors [ 50 , 51 , 102 ].…”
Section: Retinoic Acid Receptor (Rar)-dependent Signaling Is Requimentioning
confidence: 99%
“…Even though it is still not clear to what extent the teratogenic effects of EDCs in invertebrates are mediated by NRs, it has been shown that NRs are involved in embryonic and post-embryonic development in these animals [ 47 , 48 , 49 , 50 , 51 , 52 , 53 ]. Yet, the mechanisms at play are not necessarily conserved with vertebrates, revealing lineage-specific adaptions in both invertebrates and vertebrates [ 1 , 10 , 17 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 ]. The aim of this review is to describe and discuss the developmental functions of NRs in invertebrates, with a special focus on marine organisms, highlighting the particular importance of comparative approaches using emerging marine invertebrate models for the field of evolutionary developmental biology.…”
Section: Introductionmentioning
confidence: 99%
“…Despite this variance, the potential threat of ED for aquatic species is virtually ubiquitous, as illustrated by stickleback ( Pungitius pungitius Linnaeus, 1758) from remote rivers in the Arctic (St Lawrence Island, Alaska) where expression of VTG in male fish was consistent with exposure to oestrogenic PCBs – a legacy from previous military installations. Gene expression changes and DNA methylation in gonads were also allied to PCB exposure (von Hippel et al ., 2018). Higher in the food chain, terns from PCB-contaminated locations, feeding on fish and aquatic invertebrates such as molluscs and crustaceans, exhibited skewed sex ratios and elevated intersex frequencies –supporting evidence of ED and highlighting the potential threat of bioaccumulation and trophic transfer of EDCs (Hart et al ., 2003).…”
Section: Endocrine Disruption and Reproductive Effects In Aquatic Biotamentioning
confidence: 99%
“…For example, an RAR cloned from the mollusk Thais clavigera (TcRAR), failed to show transcriptional activity in response to atRA (Urushitani et al, 2013). Likewise, computational analysis of an RAR ortholog from the Pacific oyster (C. gigas), did not support atRA binding (Vogeler, Galloway, Isupov, & Bean, 2017). It was proposed that the RAR of a common ancestor of the deuterostomes and protostomes likely possessed atRA binding capabilities, but that mutations in the ligand binding domain resulted in a loss of this ability in protostomes.…”
Section: Evidence For Retinoid Signaling Machinery In Invertebratesmentioning
confidence: 99%